2018
DOI: 10.1038/s41589-018-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RNR-α antagonizes cell proliferation by directly inhibiting ZRANB3

Abstract: Since the origins of DNA-based life, the enzyme ribonucleotide reductase (RNR) has spurred proliferation because of its rate-limiting role in de novo deoxynucleoside-triphosphate (dNTP) biosynthesis. Paradoxically, the large subunit, RNR-α, of this obligatory two-component complex in mammals plays a context-specific antiproliferative role. There is little explanation for this dichotomy. Here, we show that RNR-α has a previously unrecognized DNA-replication inhibition function, leading to growth retardation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(85 citation statements)
references
References 56 publications
11
74
0
Order By: Relevance
“…Thus, we defined a PPI‐mediated downregulation of DNA synthesis that requires RNR‐α hexamerization‐promoted partial nuclear import. Consistent with the multiple gain‐of‐function concept, we found that RNR‐α nuclear translocation was suppressed by IRBIT, a known negative regulator of RNR in mammals, which also interacted selectively with hexameric RNR‐α (Figure ) …”
Section: Novel Ppis: Novel Drug Targetssupporting
confidence: 79%
See 4 more Smart Citations
“…Thus, we defined a PPI‐mediated downregulation of DNA synthesis that requires RNR‐α hexamerization‐promoted partial nuclear import. Consistent with the multiple gain‐of‐function concept, we found that RNR‐α nuclear translocation was suppressed by IRBIT, a known negative regulator of RNR in mammals, which also interacted selectively with hexameric RNR‐α (Figure ) …”
Section: Novel Ppis: Novel Drug Targetssupporting
confidence: 79%
“…[77] However,o ur genetic and biochemical data established that hexameric RNR-a partially translocated into the nucleust hrough association with importin. [76] This study also found that ZRANB3 was ap ositive regulator of DNA synthesis, and RNR-a in the nucleusdirectly bound and inhibited ZRANB3, leading to suppression of DNA synthesis. Thus, we defined aP PI-mediatedd ownregulation of DNA synthesis that requires RNR-a hexamerization-promoted partial nuclear import.…”
Section: Zranb3/rnr-amentioning
confidence: 57%
See 3 more Smart Citations